2002
DOI: 10.1002/joc.787
|View full text |Cite
|
Sign up to set email alerts
|

Millennial to multi‐decadal variability in the climate of southern Africa

Abstract: Wavelet analysis has been used to determine changes in the variability of southern Africa climate over the last three millennia. The structure of the variability in a 3000-year δ 18 O record has been compared with that in tree ring data for the last 600 years and both to the variability in annual rainfall and runoff during the 20th century. Preferred modes of variability are shown to have occurred in all the data sets. For overlap periods, the variability modes are in phase where the data are for a common seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 54 publications
6
49
0
Order By: Relevance
“…These peaks are also present in the positive values of the 24-month Standardized Precipitation Index values calculated for the northeastern interior of South Africa (Rouault and Richard, 2003). The quasi-18-year climate oscillation, according to Dyer and Tyson (1977), is confined to the subtropical latitudes south of 15°S and is clearest in the band extending from 20 to 30°S across the subcontinent (Tyson et al, 2002). This is also shown by the weakness of this oscillation in the rainfall time series at Makoholi in Zimbabwe compared to the South African stations.…”
Section: Widespread Heavy Rainfall Eventsmentioning
confidence: 78%
“…These peaks are also present in the positive values of the 24-month Standardized Precipitation Index values calculated for the northeastern interior of South Africa (Rouault and Richard, 2003). The quasi-18-year climate oscillation, according to Dyer and Tyson (1977), is confined to the subtropical latitudes south of 15°S and is clearest in the band extending from 20 to 30°S across the subcontinent (Tyson et al, 2002). This is also shown by the weakness of this oscillation in the rainfall time series at Makoholi in Zimbabwe compared to the South African stations.…”
Section: Widespread Heavy Rainfall Eventsmentioning
confidence: 78%
“…South Africa Rain is characterized by interdecadal variability between 16 and 20 years, which is observed in several studies of South African summer rainfall variability (Mason 1995;Krueger 1999;Reason et al 1996;Reason 2002;Reason and Rouault 2002;Tyson et al 2002;Jury et al 2004). Warm (cool) SST anomalies in the southwestern Indian Ocean are associated with increased (decreased) rainfall over central and eastern South Africa on seasonal to interdecadal time scales.…”
Section: Climate Of the Western Indian Ocean And Adjacent Continentsmentioning
confidence: 83%
“…11a; Holmgren et al 1999;Tyson et al 2002). A lake level record is available from Lake Malawi with annual resolution for the period 1650-1990Owen et al 1990;Johnson et al 2001).…”
Section: Southeast Africa Paleo-recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…The river is characterized by large natural floodplains attenuating the runoff and large artificial impoundments regulating the flow. The long-term flow series as well as the climate observations reveal inter-annual cycles of high, medium and low runoff with a duration varying from 10 to 80 years (Tyson et al 2002;Jury 2003;Mazvimavi & Wolski 2006). Since the runoff cycles have been reported to be primarily explained by rainfall cycles (Farquharson & Sutcliffe 1998;Beilfuss & Dos Santos 2001), the hypothesis adopted in this study is that a calibrated rainfall-runoff model will be able to reproduce the observed cycles even if not tested over the entire climate cycle.…”
Section: Study Area and Data The Zambezi River Basinmentioning
confidence: 97%